Strategi Self Management yang Efektif Bagi Mahasiswa Gen Z Analisis: Studi Literatur - Dini Setiawati; Salwa Nursinta; Sri Mulyeni (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
Higher education is now dominated by Generation Z, that refers to the group of people born between 1997 and 2012. They have been accustomed, making them highly proficient in and dependent on such technology. Although Gen Z possesses adaptive advantages within the digital ecosystem and multitasking capabilities, they face serious challenges, including a high dependency on devices and social media distractions that trigger academic procrastination. This research aims to analyze effective self-management strategies for Gen Z students to improve their academic achievement and learning independence. Through qualitative descriptive analysis technique, this study reviews existing literature by evaluating academic journals and supporting references to obtain a comprehensive picture. The results indicate that the ability to manage oneself, time, emotions, and priorities significantly determines a student`s academic success. The use of a combination of self monitoring methods, stimulus control, and self appreciation has proven effective in transforming learning habits to become more organized and increasing independence. Mastery of self-management is not only effective in reducing task procrastination but also strengthens self-efficacy and enhances the competitive quality of students in higher education. In conclusion, self-management serves as a crucial foundation for Gen Z students to balance their digital and real lives to achieve sustainable future success.